Pengaruh Current Ratio, Debt To Equity Ratio dan Return On Equity Terhadap Pertumbuhan Laba pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di BEI - Arisna .; Said Mahdani (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the effect of the current ratio, debt-to-equity ratio, and return on equity on profit growth in non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. In the world of investment and financial analysis, the stability of a company's profits is a crucial indicator in assessing the performance and sustainability prospects of a business entity. Especially in the Consumer Non-Cyclical sector, which is typically considered more resilient to economic fluctuations, investors tend to expect stable financial performance over time. However, the reality shows that not all companies in this sector have stable profit trends. The method used in this study is quantitative descriptive analysis with multiple linear regression. Secondary data in the form of data on the current ratio, debt to equity ratio and return on equity, profit growth in non-cyclical consumer companies listed on the IDX were obtained from financial reports on the website www.idx.co.id. The results of the study indicate that partially the current ratio has a negative effect on profit growth, the debt to equity ratio has no effect on profit growth and return on equity has a negative effect on profit growth. Simultaneously, the current ratio, debt to equity ratio and return on equity contribute positively and significantly to profit growth with a significance value below 0.05.